High-Resolution 3-D Radar Imaging Through Nonuniform Fast Fourier Transform (NUFFT) (Communications in Computational Physics, 2018)
This paper applies a 3-D nonuniform fast Fourier transform (NUFFT) migrationmethod to image both free-space and buried targets from data collected by a ultra-widebandground penetrating radar (GPR) system. The method incorporates the NUFFT algorithminto 3-D phase shift migration to evaluate the inverse Fourier transform more accurately andmore efficiently than the conventional migration methods. Previously, the nonuniform natureof the wavenumber space required linear interpolation before the regular fast Fouriertransform (FFT) could be applied. However, linear interpolation usually degrades the qualityof reconstructed images. The NUFFT method mitigates such errors by using high-orderspatial-varying kernels. The NUFFT migration method is utilized to reconstruct GPR imagescollected in laboratory. A plywood sheet in free space and a buried plexiglas chamberare successfully reconstructed. The results in 3-D visualization demonstrate the outstandingperformance of the method to retrieve the geometry of the objects. Several buried landminesare also scanned and reconstructed using this method. Since the images resolve the featuresof the objects well, they can be utilized to assist the landmine discrimination.